AIM and ELF bonding analyses of M–O and M–N (Metal= Ba, Y, Zr) in metal–complexes using DFT approach / Nor Ain Fathihah Abdullah, Sharizal Hasan and Lee Sin Ang - Abdullah, Nor Ain Fathihah; Hasan, Sharizal; Lee, Sin Ang (Faculty of Applied Sciences, 2021)
The molecular interaction between the chelating agents of citric acid (CA), ethylenediaminetetraacetic acid (EDTA), and triethylenetetraamine (TETA) with metals (M = Ba, Y, and Zr) were studied using Density Functional Theory (DFT) method. This study aims to determine the type of bonding between M–O/N bonds in the CA/EDTA/TETA– complexes. In this study, each metal was attached at strategic positions of chelating agents and was optimized at B3LYP/6-31G* and UGBS level of theory. The M–O bonds were characterized based on Atoms– in–molecules (AIM) and Electron Localization Function (ELF) in the topological analysis. In AIM analysis, the total electron energy density at the bond critical point (BCP) of the M–O/N bonds are used to estimate the interaction involved. The low values of ρ(r) and positive values of ∇ 2 ρ(r) indicates that ionic character exists in the M–O/N bonds. In ELF color-filled map, the blue shaded region between M–O/N atom acts as an indicator for the existence of the ionic interaction. Both AIM and ELF results confirm the existence of ionic bonding between M–O/N bonds, with values of ρ(r) and ∇ 2 ρ(r) ranging from 0.02 to 0.12 au and 0.09 to 0.5 au respectively. Further analysis on charge distribution at M–O/N bonds show that the opposite charge between Ba, Y, and Zr with O/N assured the M– O/N ionic bonding interactions